INFLIXIMAB EFFECT ON CLINICAL AND LABORATORY ACTIVITY PARAMETERS IN CASES OF VARIOUS JUVENILE ARTHRITIS VARIANTS - E.I. Alexeeva; A.M. Alekseeva; S.I. Valieva; T.M. Bzarova; R.V. Denisova ("Paediatrician" Publishers LLC, 2008)
The study analyses efficiency and safety of using mono clone antibodies for tumor necrosis factor (infliximab) for children with system (n = 21) and articular (n = 59) juvenile arthritis (JA). Infliksimab was injected intravenously (average dose of 6,8 ± 2,3 mg/kg/per injection) by a standard scheme (0, 2, 6, and each 8 following weeks). Together with antibcytokine therapy children still received immunity depressants (cyclosporine, methotraksat, leflunomid, peroral glucocorticoids). Research results prove that infliximab has pronounced hormone like anti-inflammatory effect after first injection for both patients with early and delayed articular JA variants. It reserved articular syndrome, reduced laboratory activity parameters, reduced degree of invalidity, improved quality of patients' lives. At the same time after three first infusions 88% of patients with system JA the effect was neutralized, articular syndrome activity increased, laboratory activity parameters increased, systematic indicators recurred. On the contrary, patients with both early and delayed JA variant the medication quickly and efficiently reduced activity of articular syndrome, personal estimations of pain levels and disease activity. Index of life quality was significantly improved, much like the selfbservice ability. Medication effect was registered after the first injection and remained over the whole period of observation (up to two years) in 61% cases of delayed and 93% of early articular ja variant. Thus, infliximab therapy is a reasonable, efficient and safe treatment of patients with both early and delyed articular JA. Key words: juvenile arthritis, infliximab, treatment.